2002
DOI: 10.1007/s00122-001-0808-x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance gene homologues in melon are linked to genetic loci conferring disease and pest resistance

Abstract: Genomic and cDNA fragments with homology to known disease resistance genes (RGH fragments) were cloned from Cucumis melo using degenerate-primer PCR. Fifteen homologues of the NBS-LRR gene family have been isolated. The NBS-LRR homologues show high divergence and, based on the partial NBS-fragment sequences, appear to include members of the two major subfamilies that have been described in dicot plants, one that possesses a TIR-protein element and one that lacks such a domain. Genomic organization of these seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 43 publications
(46 reference statements)
1
49
0
2
Order By: Relevance
“…Although not yet isolated at the molecular level, both Fom-1 and Fom-2 are tightly linked to sequences bearing NBS-LRR motifs (Brotman et al 2002;Wang et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet isolated at the molecular level, both Fom-1 and Fom-2 are tightly linked to sequences bearing NBS-LRR motifs (Brotman et al 2002;Wang et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Périn et al (1998) mapped this gene at 8 cM from marker T_820. Brotman et al (2002) found a RFLP marker, NBS47-3, linked at 2.6 cM to Fom-1, while another marker K_1180 flanked on the other side at 7 cM (Table 5.2). Aphids (Aphis gossypii) are another serious problem for melon because they seriously damage plants by transmitting viruses.…”
Section: A Disease Resistancementioning
confidence: 99%
“…Chemical control is ineffective because insecticide resistance is widespread. A gene (Vat) conferring resistance to this aphid has been mapped by PerlTreves' group (Klingler et al 2001;Brotman et al 2002). Vat was flanked with RFLP markers NBS-2 and AC-39 at 3.1 and 6.4 cM, respectively, using 64 F 3 families (Klingler et al 2001).…”
Section: A Disease Resistancementioning
confidence: 99%
See 2 more Smart Citations